Shaping the subculture of human source intelligence within criminal units? Testing Intelligence Analysis Groups in the French Gendarmerie - Amadio, Nicolas (Policing and society, 2023)
In response to new threats, the French Gendarmerie created Intelligence Analysis Groups within criminal units in 2017. The aim of this article is to show how IAGs are shaping a subculture of criminal intelligence through the main dynamics structuring CHIS management. Following a literature review, the first part of this paper contextualises the promotion of human intelligence in criminal units and presents the mixed approach employed. The second part demonstrates how handlers’ practices are geared toward two processes – the exploratory gathering of information followed by cleansing of such information – and require high availability, acting via three skills (cognitive, memory and empathy). The third part presents how two dimensions underpinning the handlers’ commitment (a shared belief regarding secrecy as being useful and partial autonomy) are directed through use of the ‘gray zone’ between judicial and administrative actions in order to enable judicial action.